The Effect of Yoga on the Lipid Profile: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Ghazvineh, Dorsa; Daneshvar, Mojtaba; Basirat, Vahid; Daneshzad, Elnaz (Frontiers in Nutrition, 2022)
Objectives Yoga is a mind-body stress-relieving exercise that increases mental and physical health, which may have a role in the improvement of metabolic disorders. The present study has reviewed the effect of yoga on lipid profiles as a systematic review and meta-analysis. Methods We evaluated the available randomized controlled trials on the effects of yoga-based programs, and lipid profiles by searching PubMed/Medline, Scopus, Web of Science, and the Cochrane central register of control trials up to January 2022. Both fixed and random effect analyses were used to find the relationships. Subgroup analysis was performed based on the continent, duration of the included studies, gender, and health condition of participants to discover the sources of heterogeneity. Result Fifty-three studies were included in the current systematic review and meta-analysis with a total sample size of 13,191. There was a striking association between yoga and total cholesterol (−10.31 mg/dl; 95% CI: −14.16, −6.45; I2 = 82.5%, P < 0.001), low-density lipoprotein cholesterol (−8.64 mg/dl; 95% CI: −12.03, −5.25; I2 = 75.0%, P < 0.001), high-density lipoprotein cholesterol (1.98 mg/dl; 95% CI: 0.81, 3.14; I2 = 91.6%, P < 0.001), triglycerides (−13.50 mg/dl; 95% CI: −20.09, −6.92; I2 = 90.7%, P < 0.001) and very low-density lipoprotein (−3.94 mg/dl; 95%CI: −6.31, −1.56; I2 = 72.2%, P < 0.001). Conclusion It seems yoga interventions had a substantial effect on lipid profiles, however, more qualified trials or cohort studies are needed to conclude exactly.